2016
DOI: 10.1002/ange.201606120
|View full text |Cite
|
Sign up to set email alerts
|

9‐Silafluorenyl Dichlorides as Chemically Ligating Coupling Agents and Their Application in Peptide Synthesis

Abstract: Af undamentally simple,m ild, and practical procedure for peptide bond formation is reported that employs as toichiometric amount of easy-to-access 9-silafluorenyl dichlorides as the coupling agent. Without initial preactivation or elaboration of the carboxylic acid or amine termini of the amino acids,the developed reagent is proposed to act through an unprecedented chemical ligation mechanism, bringing the two coupling partners together before being subsequently eliminated. The desired amides or peptide bonds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…They noted that with this reagent the amino acids can be tethered together (Figure 10 ), which can rearrange upon heating to give the amide bond and a siloxane polymer. 60 They observed that a dipeptide with the bulkier α-side chain on the amino ester was obtained in higher yield than a dipeptide where the bulkier α-side chain is present on the free carboxylic acid amino acid residue. Their results suggested that the first addition to the silyl coupling reagent is that of the free amine residue, and the second, is that of the free carboxylic acid residue.…”
Section: Mechanistic Investigations Of Amidationmentioning
confidence: 99%
See 3 more Smart Citations
“…They noted that with this reagent the amino acids can be tethered together (Figure 10 ), which can rearrange upon heating to give the amide bond and a siloxane polymer. 60 They observed that a dipeptide with the bulkier α-side chain on the amino ester was obtained in higher yield than a dipeptide where the bulkier α-side chain is present on the free carboxylic acid amino acid residue. Their results suggested that the first addition to the silyl coupling reagent is that of the free amine residue, and the second, is that of the free carboxylic acid residue.…”
Section: Mechanistic Investigations Of Amidationmentioning
confidence: 99%
“…These results suggested that the 9-silafluorenyl dichloride mediated amide bond formation proceeds through the chemical ligation pathway. 60…”
Section: Mechanistic Investigations Of Amidationmentioning
confidence: 99%
See 2 more Smart Citations
“…Sometimes, the activated carboxylic acids are generated in an extra step and activation requires unstable, expensive and waste‐intensive reagents. Recent advances in this field use acetylenes and a transition metal and ynamides to activate the carboxylic acid or Si ligation with 9‐silafluorenyl dichlorides . Epimerization of sensitive α‐chiral acids through the formation of oxazolone intermediates is difficult to suppress with carboxylic acid activation.…”
Section: Introductionmentioning
confidence: 99%